2015
DOI: 10.9734/ajaees/2015/18105
|View full text |Cite
|
Sign up to set email alerts
|

Level and Determinants of Women Farmers Access to Informal Credit in Abia State, Nigeria

Abstract: This work was carried out in collaboration between all authors. Author CKO designed the study, wrote the protocol and first draft, anchored the field study, gathered the initial data and edited and corrected the peer reviewed manuscript(s). Authors SIO and COE handled the statistical analysis and literature search as well as read through the edited draft. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 1 publication
6
5
1
Order By: Relevance
“…7% of the respondents are married, this implies that cultural factor of the study area may be that which encourages people to marry early. It also agrees with the findings [9,10], which states that married classes were more involved in faming because of the need to supplement, the family's means of livelihood. Table 2 shows the annual savings of respondents in the study area.…”
Section: Socio-economic Characteristics Of Farmerssupporting
confidence: 92%
“…7% of the respondents are married, this implies that cultural factor of the study area may be that which encourages people to marry early. It also agrees with the findings [9,10], which states that married classes were more involved in faming because of the need to supplement, the family's means of livelihood. Table 2 shows the annual savings of respondents in the study area.…”
Section: Socio-economic Characteristics Of Farmerssupporting
confidence: 92%
“…Literacy (ability to read and write) enables farmers to better utilize effectively and efficiently available resources in an area for increased income and welfare (Osondu et al, 2015a). High education level enhances business ideas, skills, innovation and managerial ability for business sustainability (Osondu et al, 2015b). Meanwhile, mean years of oil palm fruit processing experience of the women was 18 years, indicating that the women were well versed in oil palm fruit processing.…”
Section: Results and Discussion Socio-economic Characteristics Of Res...mentioning
confidence: 99%
“…On the other hand, household size, education level, farm size, access to training, grain and livestock producers, and age had a significant influence on level of processing. Osondu et al (2023) used multiple regressions to examine the factors influencing decision of cassava value added technologies in Nigeria. The study reported that age, education level, marital status, extension contact processing cost annual income, group membership access to credit and quantity of cassava produced had a significant effect to value addition while the adoption process was constrained by the following, inadequate capital, lack of market, inadequate access to credit inadequate knowledge of technologies, high cost of equipment and scarcity of labour.…”
Section: Literature Review On Determinants Of Crop Value Additionmentioning
confidence: 99%
“…However, value adders received a mean of 2.64 extension visits while non-value adders received an average of 1.72 contacts. Access to extension services facilitates the dissemination of new knowledge and information and consequently affects the decision to embrace agricultural technologies by smallscale agripreneurs (Osondu et al, 2023).…”
Section: Socio-economic and Institutional Characteristics Of Small-sc...mentioning
confidence: 99%